Doubly labelled water for determining total energy expenditure in adult critically ill and acute care hospitalized inpatients: A scoping review. Issue 2 (February 2022) - Tatucu-Babet, Oana A.; Nguo, Kay; Lambell, Kate J.; Romero, Lorena; Earthman, Carrie P.; Ridley, Emma J.
Summary: Background & aims: Doubly labelled water (DLW) is considered the reference standard method of measuring total energy expenditure (TEE), but there is limited information on its use in the Intensive Care Unit (ICU) and acute care setting. This scoping review aims to systematically summarize the available literature on TEE measured using DLW in these contexts. Methods: Four online databases (MEDLINE, Embase, Emcare and CINAHL) were searched up to Dec 12, 2020. Studies in English were included if they measured TEE using DLW in adults in the ICU and/or acute care setting. Key considerations, concerns and practical recommendations were identified and qualitatively synthesized. Results: The search retrieved 7582 studies and nine studies were included; one in the ICU and eight in the acute care setting. TEE was measured over 7–15-days, in predominantly clinically stable patients. DLW measurements were not commenced until four days post admission or surgery in one study and following a 10–14-day stabilization period on parenteral nutrition (PN) in three studies. Variable dosages of isotopes were administered, and several equations used to calculate TEE. Four main considerations were identified with the use of DLW in these settings: variation in background isotopic abundance; excess isotopes leaving body water as carbon dioxide or water; fluctuations in rates of isotope elimination and costs. Conclusion: A stabilization period on intravenous fluid and PN regimens is recommended prior to DLW measurement. The DLW technique can be utilized in medically stable ICU and acute care patients, with careful considerations given to protocol design.